Defining and Applying a New Approximation for the Parametric Probability Densities of Spherical Particle Profile Sizes - Poliakova, Ekaterina (Image Analysis and Stereology, 2022)
A novel approximation for the parametric probability densities of spherical particle profile diameters is suggested. The spheres are approximated from solids obtained by rotating regular polygons around their axes of symmetry. This approximation facilitates using the maximum likelihood method in samples that have too few profiles for applying classical stereological approaches.